Making the most of Musa: The role of the International Network for the Improvement of Banana and Plantain - Picq, C.; Raymond, R.; International Network for the Improvement of Banana and Plantain (1996)
The mission of the International Network for the Improvement of Banana and Plantain (INIBAP) is to increase the productivity and yield stability of banana and plantain grown on smallholdings for domestic consumption and for local and export markets. INIBAP is a programme of the International Plant Genetic Resources Institute (IPGRI). These objectives concern germplasm management and production of a better banana. Because people around the world (Latin America and the Carribbean, Asia and the Pacific, West and Central Africa, East ans Southers Africa) use Musa in so many different ways and because research needs vary from region to region, the best approach to understanding and improving banana and plantain lies in regional activities. INIBAP devote much of its effort to serving as a coordinator of such initiatives, and establish databases and neetworks by which information on Musa could be gathered, stored and distributed to a broad spectrum of users (English, French or Spanish version)